Computing branchwidth via efficient triangulations and blocks - Fomin, Fedor V.; Mazoit, Frédéric; Todinca, Ioan (Discrete Applied Mathematics, 2009)
Minimal triangulations and potential maximal cliques are the main ingredients for a number of polynomial time algorithms on different graph classes computing the treewidth of a graph. Potential maximal cliques are also the main engine of the fastest so far, exact (exponential) treewidth algorithm. Based on the recent results of Mazoit, we define the structures that can be regarded as minimal triangulations and potential maximal cliques for branchwidth: efficient triangulations and blocks. We show how blocks can be used to construct an algorithm computing the branchwidth of a graph on n vertices in time ( 2 3 ) n ⋅ n O ( 1 ) .